Redetection and description of the European dagger nematode Xiphinema diversicaudatum on peach (Prunus persica L.) in Canada - Akanwari Jerry; Yu Qing; Sultana Tahera (Journal of Nematology)
The study reports the detection of Xiphinema diversicaudatum in a peach field in Ontario, Canada. Comprehensive population characterization involved morphological and molecular analyses using 18S and 28S rDNA sequences. Morphological and molecular analysis demonstrated a close relationship between the Ontario population and those from Central Europe. This is the first report of X. diversicaudatum from peaches (Prunus persica) in Canada and in North America.